Study of Ordinal Regression Method for Supporting Factors Investigation in Stages Condition of Breast Cancer Patients in Dr. Soetomo Surabaya Hospital, Indonesia - Thania Muhammad; Destri Susilaningrum; Vidi Vianney C.M.Tanggo (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Dr. Soetomo Surabaya Hospital in 2019 received 167,000 cancer patients, and the highest was breast cancer. The increase in the stage of breast cancer is caused by the size of the tumor and how widely the cancer cells have spread to other organs. The purpose of this study was to apply the ordinal logistic regression method in the case of factors that support the condition of breast cancer stage in Dr. Soetomo Surabaya Hospital. The result of this study is that the factors that support the condition of breast cancer stages are grade and family history of breast cancer with a classification accuracy rate of 84.3%. Breast cancer patients at Dr. Soetomo Surabaya Hospital with grade 3 is likely to support staging conditions from locally advanced to advanced by 0.06 times compared to grade 1 patients. patients with grade 2 is likely to support staging conditions from locally advanced to advanced by 0.17 times compared to grade 1 patients. Patients who have a history of breast cancer in their family will have a risk of developing breast cancer with locally advanced stages to advanced stages 3.84 times than in patients with no family history of breast cancer.